ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII MTsN 2 KERINCI - Nurul Amelia; Putri Yulia (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Low mathematical problem-solving abilities can affect student learning outcomes. This study aims to determine the mathematical problem-solving skills of class VIII students of MTsN 2 Kerinci on relations and functions. The subjects in this study were students of class VII I MTsN 2 Kerinci which consisted of 21 students in one class. This study used a descriptive qualitative method. The instrument used in this research is a test of mathematical problem-solving ability. To determine the level of students' mathematical problem-solving abilities, guidelines are used which are modified from Mawaddah & Anisah's research namely the formula used to determine student scores and categories of problem-solving ability assessment results. From the results of the analysis of the data obtained, it can be concluded that the ability to solve students' mathematical problems is still in the low category. This is to the results of the questions done by students on the material relations and functions in the form of story questions where only 9.5% of students out of 21 students got quite good categories, and the rest got bad and very poor categories.